Developing Students’ Speaking Skills through Flipped Classroom Model - Imam Sudarmaji; Ariskha Ananda Amaliyah Anwar; Agus Mulyana (Universitas Bengkulu, 2021)
The aim of this study was to examine the impact of implementing flipped classroom model on students’ speaking skills. This research used quantitative method, the number of the sample were 34 of senior high school students which was taken purposively by using quasi-experimental research with before and after design. The whole online flipped classroom model was carried out, since the limitation to hold the actual face-to-face meeting at school, which still allow the students to interact face-to-face with each other and the teacher virtually through a group chat and video conferencing to discuss the material given and practicing to use spoken English during the class sessions. Pre-class activity was held using a group chat by giving instruction to the students to study the material before the actual class session and during the class session the whole class were meet face-to-face through video conferencing. A speaking test was carried before and after the implementation of flipped classroom model to assess the students’ speaking performance. Among the experimental group, the result showed the fully online flipped classroom model not only engage them with the English material but also significantly improved their speaking performance. Furthermore, the students were become more confident to speak in English during the class session.